The Implication of Constitutional Court Decision Number 36/PUU-XV/2017 on the Independence of Corruption Eradication Commission - Suparto Suparto; Dedy Gusniawan (UNIFIKASI : Jurnal Ilmu Hukum, 2020)
This study aims to find out the considerations of the Constitutional Court Judge in issuing Constitutional Court Decision No. 36/PUU-XV/2017 as well as to identify the implications of the Decision on the Independence of Corruption Eradication Commission. The method used in this study was normative juridical method. The data collected through library research were then analyzed analytic-descriptive. The formulations of the problem are; 1) What are the considerations of the Constitutional Court Judge in issuing Constitutional Court Decision No. 36/PUU-XV/2017 against judicial review of Law No. 17 of 2017 concerning MD3? and 2) What are the implications of the Constitutional Court Decision No. 36/PUU-XV/2017 against judicial review of Law No. 17 of 2017 concerning MD3 on the independence of Corruption Eradication Commission? As results, it was found that; 1) in Constitutional Court Decision No. 36/PUU-XV/2017, the Constitutional Court states that the inquiry right owned by the House of Representatives over the Corruption Eradication Commission is constitutional as long as it does not relate to the authority of investigation and prosecution owned by the Corruption Eradication Commission with the consideration that the Corruption Eradication Commission is a state institution that includes to the realm of executives; and 2) The House of Representatives will give a strong influence on the Corruption Eradication Commission even though the inquiry right owned by the House of Representatives cannot touch the authority of the Corruption Eradication Commission in conducting investigations and prosecutions. However, there is an indication that the effort to provide inquiry right is not a legal effort but rather a political effort which is widely applied in countries adhering to a parliamentary system where the parliament tends to be more dominant than the executive. Hence, it can be concluded that; 1) in this Decision, the Constitutional Court Judge did not use a stronger grammatical and systematic interpretation based on the original intense. Besides, this Decision is ambiguous and potentially contradicts with the previous Decision, namely Constitutional Court Decision No.012-016-019/PUU-IV/2006; and 2)  there will be consequences for the Corruption Eradication Commission in the future, especially in terms of independence, since it can be used as an object of inquiry right by the House of Representatives. Implikasi Putusan Mahkamah Konstitusi No. 36/Puu-Xv/2017 Terhadap Independensi Komisi Pemberantasan KorupsiTujuan dari pennelitian ini adalah untuk mengetahui pertimbangan Hakim Konstitusi dalam memutus perkara No. 36/PUU-XV/2017 dan Implikasi dari putusan tersebut terhadap Independensi Komisi Pemberantasan Korupsi. Metode penelitian yang digunakan yaitu  hukum normatif dengan cara studikepustakaan,data yang digunakan  adalah data sekunder dananalisis data dilakukan secara deskriptis analitis. Rumusan masalahnya  adalah (1). Bagaimanakah pertimbangan Hakim  Konstitusi dalam memutus perkara No. 36/PUU-XV/2017 terhadap pengujian UU No. 17 Tahun 2017 Tentang MD3 dan (2). Bagaimanakah implikasi putusan Mahkamah Konstitusi  No.36/PUU-XV/2017 terhadap pengujian UU No. 17 Tahun 2017 Tentang MD3 terhadap independensi Komisi Pemberantasan Korupsi. Berdasarkan penelitian diperoleh hasil (1) MK dalam putusan No. 36/PUU-XV/2017 menyatakan  bahwa kewenangan hak angket yang dilakukan  Dewan Perwakilan Rakyat  terhadap Komisi Pemberantasan Korupsi adalah konstitusional sepanjang tidak menyangkut kewenangan penyidikan, penyelidikan, dan penuntutan yang dimiliki oleh Komisi Pemberantasan Korupsi, dengan pertimbangan  Komisi Pemberantasan Korupsi adalah lembaga negara yang termasuk ranah eksekutif. (2). Pengaruh tekanan yang diberikan Dewan Perwakilan Rakyat  kepada Komisi Pemberantasan Korupsi akan amat kuat walaupun hak angket tersebut tidak dapat menyentuh kewenangan Komisi Pemberantasan Korupsi dalam melakukan penyidikan, penyelidikan, dan penuntutan. Namun ada indikasi bahwa upaya angket pada dasarnya bukanlah upaya hukum melainkan upaya yang bersifat politis yang banyak dipraktekkan dalam negara penganut sistem parlementer yang cenderung dominan parlemen dibanding pihak eksekutif.Kesimpulan dari penelitian ini adalah (1).  Dalam putusan ini Hakim Konstitusi tidak  menggunakan penafsiran gramatikal dan sistematis yang lebih kuat dengan berlandaskan pada original intens. Selain ituPutusan Mahkamah Konstitusi ini adalah ambigu dan  berpotensi bertentangan dengan putusan sebelumnya yaitu putusan  Mahkamah Konstitusi  No.012-016-019/PUU-IV/2006.(2)  Adanya konsekuensi bagi Komisi Pemberantasan Korupsi dimasa mendatang khususnya dalam hal independensi  akibatdari dapat dijadikannya objek hak angket oleh Dewan Perwakilan Rakyat